Political Capital, Women's Representation, and Electability in Jambi’s 2024-2029 Provincial Legislative Elections - Mariatul Qibtiyah; Beriansyah, Alva; Elsi, Sutri Destemi; Muliono (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Women’s participation in Indonesian electoral politics has increased following affirmative quota policies, yet this numerical inclusion has not been fully reflected in women’s electoral success. This article examines the role of political capital in shaping women’s representation and electability in the 2024-2029 Jambi Provincial Legislative Council election. The study addresses the gap between formal candidacy and actual electability by analyzing how female candidates accumulate and convert political capital in a local electoral context. Using a qualitative descriptive-analytical approach, this research applies Casey’s political capital framework, consisting of institutional, social, cultural, economic, and symbolic capital. The findings show that women accounted for 247 of 732 legislative candidates, or 33.74%, but only seven of 55 elected legislators, or 12.72%, were women. This indicates a significant gap between affirmative representation and electoral outcomes. The elected female candidates generally possessed strong party support, extensive social networks, credible educational and professional backgrounds, sufficient economic resources, and symbolic legitimacy rooted in public reputation, family networks, or local social recognition. The study argues that women’s electability depends not only on affirmative policies but also on their capacity to strategically manage and convert different forms of political capital. This article contributes to gender and politics studies by showing that women’s political representation at the local level is shaped by the interaction between institutional rules, social structures, and candidates’ political resources.